Clinical implications of changes in the diversity of c-MYC copy number variation after neoadjuvant chemotherapy in breast cancer. Issue 1 (December 2018) - Chung, Yul; Kim, Hyun; Kim, Milim; Ahn, Soomin; Park, So
Abstract Chemotherapy can alter the makeup of a tumor cell population by exerting selection pressure. We examined the change in Shannon index, a mathematical diversity measure used in ecology, forc-MYC copy number variation (CNV) after neoadjuvant chemotherapy and evaluated its clinical significance in breast cancer. Associations between Shannon indices forc-MYC CNV in pre- and post-neoadjuvant chemotherapy breast cancer samples and clinicopathologic features of tumors as well as patient survival were analyzed in 144 patients. A change inc-MYC amplification and copy number gain status was found in 14.3% and 33.6% with most cases showing positive to negative conversion. The chemo-sensitive group showed a significant decrease in Shannon index after neoadjuvant chemotherapy. However, there was no difference in diversity indices between pre- and post-neoadjuvant chemotherapy specimens in the chemo-resistant group. In survival analyses, high Shannon indices forc-MYC CNV in post-neoadjuvant chemotherapy samples as well as those in pre-neoadjuvant chemotherapy samples were revealed as independent prognostic factors for poor disease-free survival not only in the whole group but also in the chemo-resistant subgroup. These findings suggest that a change in Shannon index forc-MYC CNV after neoadjuvant chemotherapy reflects chemo-responsiveness and that Shannon indices after neoadjuvant chemotherapy have a prognostic value in breast cancer patients who receive neoadjuvant chemotherapy.